Market as Religion: The Dynamics of Business Network in Megachurches - Roberto Bazanini; Celso Machado (BBR: Brazilian Business Review)
Contemporaneously, in market view, the market of symbolic goods of religion is characterized by the pluralism of options that the postmodern individual has to join religious institutions. In this scenerie, it establishes a situation of fierce rivalry for the achievement of competitive advantage. The according exploratory and qualitative research aimed at analyzing the marketing strategies developed by the IURD leaders with their stakeholders in the Solomon’s Temple. The results show that in the competitive market of symbolic goods of religion, the magnitude and sumptuousness of megatemples construct a brand image that places the theological concerns of a future life or of salvation in the background, prioritizing practical solutions to everyday problems .The contribution of the research is to explain how the neopentescostal churches reinterpret traditional values of religiosity, by accepting with naturalness what had been rejected by traditional Protestantism and, thus, to consolidate and at the same time to legitimize the new dynamics of the religions that they act with the logic of the market.